Guidelines to Prevent Malevolent Use of Biomedical Research - Green, Shane K. (Cambridge quarterly of healthcare ethics, 2006)
In February 1975, a group of leading scientists, physicians, and policymakers convened at Asilomar, California, to consider the safety of proceeding with recombinant DNA research. The excitement generated by the promise of this new technology was counterbalanced by concerns regarding dangers that might arise from it, including the potential for accidental release of genetically modified organisms into the environment. Guidelines developed at the conference to direct future research endeavors had several consequences. They permitted research to resume, bringing to an end the voluntary moratorium that the National Academy of Sciences (NAS) had instituted several months earlier. They also served to illustrate that the scientific community was capable of self-governance, thereby securing public trust and persuading Congress not to institute legislative restrictions. Finally, they underscored the importance of weighing unforeseen risks inherent in some research against potential benefits that may arise from these same endeavors.The Council on Ethical and Judicial Affairs of the American Medical Association (AMA) formulates ethical policies for the medical profession through its interpretations of the AMA's Principles of Medical Ethics. The Council at the time this report was adopted consisted of Michael S. Goldrich, M.D. (Chair); Priscilla Ray, M.D. (Vice-Chair); Regina M. Benjamin, M.D., M.B.A.; Daniel Higginson (student member); Mark A. Levine, M.D.; John M. O'Bannon III, M.D.; Robert M. Sade, M.D.; Monique A. Spillman, M.D., Ph.D. (resident member); and Dudley M. Stewart, Jr., M.D. Staff to the Council at the time the report was adopted were Audiey Kao, M.D., Ph.D. (Vice President, Ethics Standards Group); Karine Morin, L.L.M. (Secretary); and Sara Taub, M.Be. Shane K. Green, Ph.D., was a Fellow in the AMA's Institute for Ethics.